(3GdTGaj aj TQM eSfO GdTGaYis - (3GdeHGQc Hf eMeO Hf eMeO Hf eMeO Hf nYrHO GdncpQje GdTjHGfqj GdLRQj, CHh GdSYGOGJ, eLO GdOjf, GHf GdCKjQ,J (B606 (3g` s; (3CHh YHO Gddg eMeO Hf GOQjS GdTGaYjs
(3ChdgG (B:s
(3UdGJc hdh fbd ecGfkG MJi ScJ Ydi bhdg GdaQY GdKGfi ai Chdi GdfGS HGdEeGeI s
(3BNQgG (B:s
(3CNQLg GdTGaYi ai GdEHJOGA HbVGA Ojhf GdejJ HYO GdaQGZ ef JLfjRg hOafg GfJgi GdLRA GdKGfi ef cJGH GdTGaYi ai TQM eSfO GdTGaYi s
(3cJHJ HYV GdcdeGJ HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdMOjK h GdeUWdMs